WHISTLEBLOWING PADA INDUSTRI PERBANKAN DI INDONESIA - Ripa Fajarina Laming; Nur Fadhila Amri (SIMAK, 2021)
This study aims to analyze the effect of whistleblowing hotline on internal fraud in the banking industry in Indonesia and to further examine whether the whistleblowing hotline can limit fraud. Observations were made over a period of 10 years. The sample in this study was 270 banking companies listed on the Indonesia Stock Exchange (IDX) which were determined through purposive sampling technique. The research data uses the company's annual report for the 2010-2019 period obtained from the Indonesia Stock Exchange (IDX) and Good Corporate Governance data obtained from the company's official website. The analytical method used is linear regression using SPSS software. The results showed that the whistleblowing hotline had a significant negative effect on internal fraud. However, in order for the whistleblowing hotline to run effectively, adequate resources are needed in managing the hotline and definite legal protection for whistleblowers.